Handbook of research on effective communication, leadership, and conflict resolution (Advances in linguistics and communication studies (ALCS) book series, 2016)
"This book evaluates operational strategies and interpersonal skill development for the successful management of modern organizations, highlighting various governance and interaction techniques that assist in mediating organizational controversies"--Provided by publisher